Microestrutra e caracterização dielétrica da solução sólida Sr3WxMo1-xO6(0 ≤ x ≤ 1,0) - Magalhães, Ticiane Alencar (2017)
The oxides of the double perovskite type have relevant properties, such as moderate-high relative dielectric permittivity (ɛ r ), low dielectric loss tangent (tan δ) and good thermal stability. These have been extensively studied by solid-state physics for technological purposes. In this sense, this work approaches the route of obtaining the solid solution Sr 3 W x Mo 1-x O 6 (0 ≤ x ≤ 1,0) by solid state reaction, where the crystalline phases were confirmed by powder X-ray diffraction (PXRD). The variation in the concentrations of Mo and W was carried out in order to study this influence on the dielectric properties of the final material. A ɛ r and tan δ decreased with increasing signal frequency applied to all samples at room temperature. Another important aspect is that, with the additions of W, there was a decrease in ɛ r and tan δ. However, the highest values were for the samples with x = 0.8; x = 0.9 and Sr 3 WO 6 (SWO). It was observed that the value of ɛ r increases with increasing temperature. Additionally, was observed the presence of temperature-dependent dielectric relaxation, where the relaxation times (τ) decrease with increasing temperature. The activation energy (E a ) measurements obtained through the real conductivity component (σ’) and imaginary components of the impedance (Z”) and electrical modulus (M”), with temperature variation, were attributed to the same thermo-activated process due to obtaining close values. For the permittivity temperature coefficient (TCɛ) were obtained values with variations in the low and high frequency regions for all the samples, where the additions of 0.4 to 0.6 W showed little dependence. Through the data of the Nyquist diagram was identified the presence of relaxation processes, modeled by R-CPE circuits in parallel, in order to know the contributions of grain, grain boundary and electrode-sample interface. Therefore, the electrical processes in the material depend on the temperature and are the result of the relaxation phenomena. Thus, the importance of the oxides synthesized for the application as capacitive elements with moderate ɛ r and low tan δ was confirmed, presenting small variations with the increase of the temperature, within the region of frequency of 100 Hz - 1 MHz.